A concepção de pessoa na teoria da justiça de Martha C. Nussbaum - Partchel, Jaison Matias (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation aims to provide a description of the conception of person found in Martha C. Nussbaum's theory of justice, as well as to determine whether the moral realism present in this theory can be compatible with the acknowledgment of the tragic element of the conception of person. To that end, the methods used were the conceptual analysis based on bibliographic research of primary theoretical sources, such as Nussbaum herself, John Rawls and Amartya Sen, as well as secondary ones, such as commentators relevant to the subject. The research problem was narrowed down as follows: Is it possible to reconcile Nussbaum's moral realism with a theory of justice that does not incur a comprehensive conception of the good? In other words, is it possible to avoid a kind of paternalistic perfectionism when approaching capabilities, considering its notion of pre-political rights? Following this scope, this dissertation extracted results that have identified an ecumenical view of person in Nussbaum's theory of justice, as well as confirmed the hypothesis raised regarding the tragic dimension of the person, concluding that the notion of person is a mixed notion, contextual, social, and traversed by a tragic element and animal condition and from the point of view of political normativity.
Keywords: Justiça; Florescimento; Liberalismo; Nussbaum; Capabilidades; Justice; Flourishing; Liberalism; Capabilities; ACCNPQ::Ciências Humanas::Filosofia